Evolution of Combined Impaired Fasting Glucose and Impaired Glucose Tolerance in β-Thalassemia Major: Results in 58 Patients with a Mean 7.7- year Follow-Up: Evolution of prediabetes in β-Thalassemia Major - De Sanctis, Vincenzo; Daar , Shahina; Soliman , Ashraf T; Tzoulis , Ploutarchos; Yassin, Mohamed A.; Kattamis , Christos (Acta Biomedica Atenei Parmensis, 2022)
Abstract. Background: Advances in β- thalassemia major (β-TM) care have transformed a disease which had previously led to an early childhood death into a chronic condition. With increased lifespan, comorbidities associated with the disease have become more common, among them glucose dysregulation (GD) which develops insidiously, aggravating prognosis and patients’ quality of life. Objectives: The objectives of this study were to retrospectively review the extent to which β-TM patients, having combined impaired fasting glucose (IFG) and impaired glucose tolerance test (IGT) on oral glucose tolerance test (OGTT), progressed to diabetes and to analyze the potential determinants inducing this progression, or regression to normal glucose tolerance test (NGT). Research design and method: Data of 58 β-TM patients, followed for a mean duration of 7.7 years (range: 1-20 years) with annual or biennial OGTT, were retrieved. Insulin release and insulin sensitivity (IS) were also analyzed. Results: During the follow-up, FPG and 2-h PG levels after OGTT reverted to NGT in 13 patients (22.4%), deteriorated in 13 patients (22.4%) who developed diabetes mellitus, and did not change in the remaining 32 patients (55.2%). A significant correlation was observed between FPG and ALT level (r: 0.3158; P:0.01) and an inverse correlation was found between chronological age and serum ferritin (SF) level (r: -0.321; P:0.014). Finally, SF and ALT, both at the baseline and at the time of last observation, were independent predictors of evolution to diabetes mellitus. Conclusion: The combination IFG/IGT in β-TM patients with severe iron overload constitutes a high-risk state for developing diabetes.